A compassion focused intervention for trait perfectionism in non-clinical settings: a pilot study - Birni, Gaye; Satici, Begum (SPRINGER, 2024)
Individuals' well-being can be jeopardized by perfectionism. Previous studies show that pursuing perfection can increase stress and anxiety, and it is linked with many mental disorders. Literature suggests that perfectionists may struggle to express compassion to themselves and others. Compassion interventions with perfectionists can assist them in coping with trait perfectionism and the challenges that it brings. In this pilot study, an 8-week compassion-focused psychoeducational intervention program was developed and implemented with the intervention group in a non-clinical setting. In addition, a 6-week placebo group and a control group with no intervention were formed. According to the pre-test and post-test results, there was no significant change in the placebo and control groups, but the perfectionism levels of the intervention group decreased and compassion levels increased. In addition, there was no difference between intervention group's 3-month follow-up and post-test results, indicating that the effect of the intervention continued after the intervention. In this pilot study, the compassion-focused intervention program helped individuals with their perfectionism and fears of compassion. In addition, showing compassion to oneself enhanced feelings of self-worth in the intervention group. The intervention program can be studied in larger groups for further understanding of its affect in trait perfectionism.
Keywords: Perfectionism; Self-compassion; Fears of compassion; Compassion intervention; RANDOMIZED CONTROLLED-TRIAL; THERAPY; VALIDITY; ESTEEM; SCALE; Psychology